Risk factors for fluoroquinolone-resistant Escherichia coli in adults with community-onset febrile urinary tract infection - van der Starre, W. E.; van Nieuwkoop, C.; Paltansing, S.; van't Wout, J. W.; Groeneveld, G. H.; Becker, M. J.; Koster, T.; Wattel-Louis, G. H.; Delfos, N. M.; Ablij, H. C.; Leyten, E. M. S.; Blom, J. W.; et al. (Journal of antimicrobial chemotherapy, 2011)
To assess risk factors for fluoroquinolone resistance in community-onset febrile Escherichia coli urinary tract infection (UTI). A nested case-control study within a cohort of consecutive adults with febrile UTI presenting at primary healthcare centres or emergency departments during January 2004 through December 2009. Resistance was defined using EUCAST criteria (ciprofloxacin MIC >1.0 mg/L). Cases were subjects with fluoroquinolone-resistant E. coli, and controls those with fluoroquinolone-susceptible isolates. Multivariable logistic regression analysis was used to identify potential risk factors for fluoroquinolone resistance. Of 787 consecutive patients, 420 had E. coli-positive urine cultures. Of these, 51 (12%) were fluoroquinolone resistant. Independent risk factors for fluoroquinolone resistance were urinary catheter [odds ratio (OR) 3.1; 95% confidence interval (CI) 0.9-11.6], recent hospitalization (OR 2.0; 95% CI 1.0-4.3) and fluoroquinolone use in the past 6 months (OR 17.5; 95% CI 6.0-50.7). Environmental factors (e.g. contact with animals or hospitalized household members) were not associated with fluoroquinolone resistance. Of fluoroquinolone-resistant strains, 33% were resistant to amoxicillin/clavulanate and 65% to trimethoprim/sulfamethoxazole; 14% were extended-spectrum β-lactamase (ESBL) positive compared with <1% of fluoroquinolone-susceptible isolates. Recent hospitalization, urinary catheter and fluoroquinolone use in the past 6 months were independent risk factors for fluoroquinolone resistance in community-onset febrile E. coli UTI. Contact with animals or hospitalized household members was not associated with fluoroquinolone resistance. Fluoroquinolone resistance may be a marker of broader resistance, including ESBL positivity.